3D/4D multiscale imaging in acute lymphoblastic leukemia cells-visualizing dynamics of cell death - Sarangapani, Sreelatha (2018)
Quantitative phase detection is a new methodology that provides quantitative information on cellular morphology to monitor the cell status, drug response and toxicity. In this paper the morphological changes in acute leukemia cells treated with chitosan were detected using d’Bioimager a robust imaging system. Quantitative phase image of the cells was obtained with numerical analysis. Results show that the average area and optical volume of the chitosan treated cells is significantly reduced when compared with the control cells, which reveals the effect of chitosan on the cancer cells. From the results it can be attributed that d’Bioimager can be used as a non-invasive imaging alternative to measure the morphological changes of the living cells in real time.